Domination and Intimidation as Forms of Symbolic Violence in Adolescent Dating Relationships - Apriantika, Sasiana Gilar; Hendrastomo, Grendi; Agustina, Dwi; Hidayah, Nur (JSW (Jurnal Sosiologi Walisongo), 2023)
The National Commission on Violence Against Women in Annual Record Data 2021 stated that there were 1309 cases of violence in personal relationships in 2020. Among these cases, psychological, physical, and sexual aggression is the most prevalent. This research aims to explore what forms of violence in dating, i.e., domination and intimidation, are experienced by adolescents. This research uses a qualitative approach, with data collected through survey methods. The findings show that domination and intimidation are experienced by more than half of adolescents in dating relationships. The two forms of domination are expectations from and sacrifice for a partner. Meanwhile, the forms of intimidation are speaking in a high tone, threatening, and inflicting fear to do something without the partner’s permission. This violence continues perpetuating, with Doxic through rules that are never considered coercion. This research has implications for educating the adolescents about various forms of violence in relationship that are often considered as a normal things.